Lipid–protein forces predict conformational changes in a mechanosensitive channel - Csaba Daday; Bert L. de Groot (European Biophysics Journal, 2021)
The mechanosensitive TREK-2 potassium channel, a member of the K2P family, has essential physiological roles and is, therefore, a pharmaceutical target. A combination of experimental and computational studies have established that of the two known conformations, “up” and “down”, membrane tension directly favors the “up” state, which displays a higher conductance. However, these studies did not reveal the exact mechanism by which the membrane affects the channel conformation. In this work, we show that changes in protein–lipid interaction patterns suffice in predicting this conformational change, and pinpoint potentially important residues involved in this phenomenon.

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)